Pemanfaatan Pekarangan Rumah untuk Teknologi Hidroponik dengan Greenhouse - Elis Nurhayati; Mega Nur Prabawati; Eva Mulyani; Ike Natalliasari (LSM Catimore dan Sahabat, 2024)
Community Service The Program for Implementing Science and Technology in the Community (PbM-PPIM) aims at several things, including motivating and providing education to the community about the importance of meeting food intake needs independently, optimizing Hydroponic technology by building a Greenhouse. To achieve this goal, this program will provide materials and tools in the form of Greenhouses, such as iron, paranet, UV plastic, paralon, netpots, rockwool, water pumps, etc., as well as vegetable seeds to the community.. The method that will be used in this program is through patterned and structured outreach activities by providing information and education to the public about Hydroponic technology and Greenhouse construction. Apart from that, this program will also provide ongoing assistance and evaluation to the community so that they can maximize vegetable production using Hydroponic technology and minimize plant pests. Thus, it is hoped that this program can help the community improve food security and the family economy through Hydroponic technology and Greenhouse construction.